Coordination and relationships between organisations during the civil–military international response against Ebola in Sierra Leone: an observational discussion. Issue 3 (25th March 2016) - Forestier, Colleen; Cox, A T; Horne, S
Abstract : The Ebola virus disease (EVD) crisis in West Africa began in March 2014. At the beginning of the outbreak, no one could have predicted just how far-reaching its effects would be. The EVD epidemic proved to be a unique and unusual humanitarian and public health crisis. It caused worldwide fear that impeded the rapid response required to contain it early. The situation in Sierra Leone (SL) forced the formation of a unique series of civil–military interagency relationships to be formed in order to halt the epidemic. Civil–military cooperation in humanitarian situations is not unique to this crisis; however, the slow response, the unusual nature of the battle itself and the uncertainty of the framework required to fight this deadly virus created a situation that forced civilian and military organisations to form distinct, cooperative relationships. The unique nature of the Ebola virus necessitated a steering away from normal civil–military relationships and standard pillar responses. National and international non-governmental organisations (NGOs), Department for International Development (DFID) and the SL and UK militaries were required to disable this deadly virus (as of 7 November 2015, SL was declared EVD free). This paper draws on personal experiences and preliminary distillation of information gathered in formal interviews. It discusses some of the interesting features of the interagency relationships, particularly between the military, the UK's DFID, international organisations, NGOs and departments of the SL government. The focus is on how these relationships were key to achieving a coordinated solution to EVD in SL both on the ground and within the larger organisational structure. It also discusses how these relationships needed to rapidly evolve and change along with the epidemiological curve.